Применение оптимизационных задач в планировании работы грузового автотранспортного предприятия - Ludmila Semenovna Trofimova; Vadim Valentinovich Anokhin (Вестник СибАДИ, 2017)
The article presents the results of the analysis, which allowed to establish that previous studies the use of optimization problems was the way forward but on the operational planning of rolling stock and long-term planning of development of production and technical bases and repair, transport powerfully-stay accommodation. As a performance criterion, typically used costs rather than profit from the conditions of contracts. Previously performance criteria to be determined were Offered individually for commercial and technical exploitation, rather than for enterprises in General.